New insights into taphonomic analysis of the Upper Pleistocene Ursus spelaeus bone deposit from Bàsura cave (Toirano, NW Italy). (7th March 2022) - Zunino, Marta; Starnini, Elisabetta; Arobba, Daniele; Avanzini, Marco; Citton, Paolo; Firpo, Marco; Negrino, Fabio; Romano, Marco; Salvador, Isabella; Rellini, Ivano
ABSTRACT: Bàsura Cave (Toirano, NW Italy) became famous worldwide in 1950 for the discovery of prehistoric human footprints and of an impressive Ursus spelaeus bone deposit baptized by the first explorers 'Cimitero degli Orsi' (Bear Cemetery). Bear remains belonging to the deeper layer of the deposit have been left in situ and are now one of the principal attractions for visitors. A new research project aimed at re‐evaluating the legacy and collections from this important cave involved the taphonomic study of the bones, along with sedimentological and micromorphological analyses and new radiocarbon dates to understand the nature and chronology of the deposit. In the present study, element quantification and state of preservation of bone surfaces displayed by distinct skeletal elements were analysed to assess the origin of bone accumulation, the composition of the assemblage in terms of age and species, and the representation of the different portions of the carcasses. Bone sorting, the orientation of skeletal elements along with oxidation pattern and micromorphological data indicate intense reworking of sediments and bones. The site can be considered among those known in Europe as representative of the last populations of U. spelaeus before the demise of this species during the Last Glacial Maximum.